2021
DOI: 10.1111/famp.12628
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Diverse Populations in Couple and Family Therapy Intervention Studies: A Systematic Review of Race/Ethnicity, Sexual Orientation, Age, and Income in the United States from 2014 to 2019

Abstract: Disparities in mental health care among marginalized populations have been welldocumented. Without research designed to study interventions for diverse populations, disparities in the quality of services will persist. A systematic review of articles evaluating couple and family therapy (CFT) interventions was conducted to evaluate the representation of diverse populations. More specifically, researchers sought to examine race/ethnicity, sexual orientation, income level, and age of sample participants. One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 54 publications
1
27
1
Order By: Relevance
“…Specific to representation, Sprenkle's (2012) review of CFT efficacy and effectiveness research from 2001 to 2011 revealed that inclusion of non-European American participants was most prevalent in the adolescent drug abuse literature, followed by the literature on conduct disorder, family psychoeducation for major mental illness, relationship education, and child/adolescent disorders. Tseng et al (2021) review of CFT interventions in 10 journals revealed nuances surrounding greater representation of racial and ethnic diversity in family therapy research compared to couple therapy research. In both areas, African American and Latinx groups were more frequently represented in studies than other racial and ethnic groups (Tseng et al, 2021).…”
Section: Cultural Diversity and Social Justice Issues In Couple And Family Intervention Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific to representation, Sprenkle's (2012) review of CFT efficacy and effectiveness research from 2001 to 2011 revealed that inclusion of non-European American participants was most prevalent in the adolescent drug abuse literature, followed by the literature on conduct disorder, family psychoeducation for major mental illness, relationship education, and child/adolescent disorders. Tseng et al (2021) review of CFT interventions in 10 journals revealed nuances surrounding greater representation of racial and ethnic diversity in family therapy research compared to couple therapy research. In both areas, African American and Latinx groups were more frequently represented in studies than other racial and ethnic groups (Tseng et al, 2021).…”
Section: Cultural Diversity and Social Justice Issues In Couple And Family Intervention Researchmentioning
confidence: 99%
“…Tseng et al (2021) review of CFT interventions in 10 journals revealed nuances surrounding greater representation of racial and ethnic diversity in family therapy research compared to couple therapy research. In both areas, African American and Latinx groups were more frequently represented in studies than other racial and ethnic groups (Tseng et al, 2021). Alongside evident progress, significant work remains to increase representation and improve upon critically conscious engagement and intervention strategies with racially and ethnically diverse couples and families.…”
Section: Cultural Diversity and Social Justice Issues In Couple And Family Intervention Researchmentioning
confidence: 99%
“…Both the sample and the human observational coders can be biased. The sample can be biased because a swath of the population (e.g., those from non-White racial/ethnic groups, sexual and gender minority couples, low-income couples, rural couples, and individuals in late adulthood) are generally underrepresented in couple research (e.g., Hartwell et al, 2017; Karney et al, 2004; Tseng et al, 2021; Williamson et al, 2022). With few minority couples in the training data, the algorithm may not have a sufficient sample of behavior in those couples, leading to less accurate behavior classifications for minority couples.…”
Section: Discussionmentioning
confidence: 99%
“…The historical trend to focus on white middle class couples is reflected in studies of clients in couple therapy research(Tseng et al, 2021).…”
mentioning
confidence: 99%